1991
DOI: 10.1017/s0269964800001881
|View full text |Cite
|
Sign up to set email alerts
|

Limiting Distributions for Path Lengths in Recursive Trees

Abstract: The depth of insertion and the internal path length of recursive trees are studied. Luc Devroye has recently shown that the depth of insertion in recursive trees is asymptotically normal. We give a direct alternative elementary proof of this fact. Furthermore, via the theory of martingales, we show that In, the internal path length of a recursive tree of order n, converges to a limiting distribution. In fact, we show that there exists a random variable I such that (In – n In n)/n→I almost surely and in quadrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 6 publications
(8 reference statements)
6
49
0
Order By: Relevance
“…This result is already known; see Mahmoud (1991) and Dobrow and Fill (1999). However, our approach also gives…”
Section: Total Path Lengthsupporting
confidence: 75%
“…This result is already known; see Mahmoud (1991) and Dobrow and Fill (1999). However, our approach also gives…”
Section: Total Path Lengthsupporting
confidence: 75%
“…where we used results from [9] for the asymptotic average total path length of such a collection of large blocks.…”
mentioning
confidence: 99%
“…is the limit distribution of the internal path length of the random recursive tree, that has been obtained by martingale methods by Mahmoud [11] and by the contraction method by Dobrow and Fill [4]. In particular, in [4] it is shown that (X…”
Section: Consequently E[h (ϑ)mentioning
confidence: 99%